SAT0735-HPR Patients' assessment of the applicability of the ultrasound image method. (15th June 2017) - Mendonça, JA; Ferreira, WH Rodrigues; Laurindo, IMM
Abstract : Background: The applicability of ultrasonography in diagnosis and monitoring of rheumatic diseases has been steadily growing but little is known about the patient's perspective. Objectives: To assess the patient's knowledge of the ultrasound (US) method and its clinical applicability as well as to evaluate how much was learned after a lecture. Methods: Patients with rheumatic diseases were invited to an educational meeting that included an US lecture. They were asked to fill out a questionnaire before and after the 35-minute lecture about US and its clinical uses. The questionnaire included questions about their disease and treatment, their educational background (years of study) and ten questions about US and its clinical uses (table).These ten questions had to be answered with "yes", "no", or "I am not sure" . Results: A total of 70 patients attended the lecture and answered the questionnaires. Their demographic characteristics were as follows: Mean ± SD: age 63±12 years, disease duration: 9.6±0.8 years, the most frequent self- reported diagnosis was rheumatoid arthritis (57, 2%), while osteoarthritis accounted for another 20%. Most patients had only eight years of study (64.3%) and a university degree was reported by 14%. The questionnaire responses of 66 patients with rheumatic diseases were analysed. There was a noticeable increase in the positive responses to these questions: 1, 2, 3 and 7, after the lecture, 44% (p=0.001); 29% (p=0.001); 10% (p=0.06); 27% (p=0.009), respectively. Although only 26% of the patients have had an articular US, in 65% it led to a change in treatment. Positive answers to some questions, which were perhaps too complex, showed a discrete increase, less than 10%, conceivably due to the surprisingly high background of positive answers. Conclusions: As expected, the US image method was familiar to most but not its applicability in articular diseases. After the lecture there was an increase in understanding of the positive impact of US in rheumatic diseases, implying that short and focused lectures are a useful tool in educational programs for patients. Disclosure of Interest: None declared